Pengaruh Model Pembelajaran PJBL Terhadap Hasil Belajar Berguling Belakang pada Peserta Didik - Sri Gusti Handayani; Rezli Oktaviani; Anton Komaini; Sepriadi Sepriadi; Heru Andika (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
The low learning outcomes of students on the backward roll material are an obstacle in floor gymnastics material for Physical Education learning, based on the dominance of conventional approaches that do not involve student activities. Therefore, an innovative learning model is needed that can increase student involvement in learning outcomes. This study aims to analyze the effect of the Project Based Learning (PjBL) learning model on backward roll learning outcomes at SDN 31 Ambacang. The method used is a quasi-experimental with a One-Group Pretest–Posttest design, 13 students were involved. Data were collected through pre-test and post-test, followed by descriptive and inferential analysis. The results showed an increase in the average score from 67.23 in the pre-test to 87.31 in the post-test with an N-Gain value of 61.35% which is in the medium to high category. These findings indicate that the implementation of PjBL is effective in improving learning outcomes, encouraging active involvement, collaboration, and reflection of students in the learning process. This study has design limitations due to the lack of a control group and a relatively small sample size, which limits generalizability. Future research is recommended to use an experimental design with a comparison group and involve a larger sample size to obtain more comprehensive results.